PURIFICATION AND CHARACTERISATION OF IMMUNOGLOBULINS FROM THE SERUM OF A CATFISH, CLARIAS GARIEPINUS (BURCHELL, 1822) - Rathore, Gaurav; Swaminathan, T. Raja; Rashee, Shaista; Parvez, Najeeb; Mastan, S. A.; Qureshi, T . A. (Journal of Indian Fisheries Association, 2015)
Attempts have been made to characterize and purify immunoglobulins from the serum of Clarias gariepinus, which has been immunized with bovine serum albumen. Initially, the proteins in the serum were chromatographed successively by affinity chromatography column. The affinity-purified fraction was concentrated and checked in SDS-PAGE, two bands of heavy chain and two bands of light chain were observed. Since teleost immunoglobulins have been shown to belong to a single class, the extra bands in light and heavy chains in the present study might be the breakdown of immunoglobulin or some unpurified contaminants. The affinity-purified fraction was also subjected to gel filtration chromatography column. Keywords: Clarias gariepinus, Immunoglobulin, Serum.